Organic Tolerance and Harmony in the Pesantren Bali Bina Insani - Muhammad Fahmi; Masdar Hilmy; Senata Adi Prasetia (Ulumuna, 2022)
This paper describes the organic tolerance, capital, and management of harmony at a pesantren of the Muslim minority in Bali, Indonesia. The pesantren is Bali Bina Insani (BBI) in which there are Muslim and Hindu teachers. The organic tolerance, capital, and management of harmony with the accommodation of some Hindu teachers is a certainty. Data collection was carried out through documentation, participant observation, and in-depth interviews, then qualitatively analyzed. The results showed that the capital of the pesantren in harmonizing Muslim and Hindu teachers is tolerant (tasāmuh) and inclusive. Aligned with the pesantren's vision and mission is realizing Islam raḥmah li al-‘ālamīn in all community services and making friends with all people regardless of ethnic, racial, cultural, and religious diversity. In this context, organic tolerance which was developed by pesantren is a certainty. Also, the management of harmony has been implemented professionally. The pesantren does not emphasize religious symbols, but it concerns the essence of Islamic orthodoxy. The pesantren management never questioned the differences of ethnic, racial, cultural, and religious of some teachers. For them, the most important thing is doing their jobs very well and professionally according to their authority. So, the harmony in this pesantren is organic.